Peranan Badan Usaha Milik Desa (Bumdes) Pada Kesejahteraan Masyarakat Pedesaan ( Studi Kasus Pada Bumdes Di Kabupaten Mempawah, Kalimantan Barat) - Sunaryono; Muhammad Salahuddin; Zulka Sapta Dilla (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2019)
This study aims to analyze the existence of Village-Owned Enterprises (BUMDes) on community welfare. This research uses the Community Based Research method, which consists of 3 stages including: a. indepth interview stage with participants who are key actors in BUMDes, b. the stage of group discussion based on the interest groups in the village, and c. the FGD (Focus Group Discussion) phase where the discussion is carried out by all interested parties. All this was done to validate and verify the findings in the previous stage. The results of this study indicate the presence of BUMDes has had an impact on changes in the economic and social fields of rural communities. Although it has not been able to provide significant benefits for improving the welfare of villagers directly, it has slowly been able to provide solutions to several problems, especially related to the marketing of superior products and employment.